EVALUATING COLOR AND SHAPE AS THE VISUAL ELEMENTS IN ORDER TO PROMOTE LABUAN BAJO - Rachmawati, Rizka (Universitas Pendidikan Indonesia (UPI), 2023)
In recent years, Labuan Bajo has experienced significant growth and continues to grow in terms of attracting domestic and foreign tourists. This is supported by the role of advertising media that developed in society. In previous research, it was stated that the visual elements in the promotion poster were an important factor in depicting the beautiful island situation in Labuan Bajo. The aim of this research is to determine the kind of visual elements in promotion media to represent the potential of Labuan Bajo. The qualitative method is used by doing literature review and experiment, this was supported by data collecting analysis of the posters from 30 graphic designers. The result of visual elements research is conducting the illustration shape and colour by the Labuan Bajo posters. Then, it is expected not only to become valuable elements for Labuan Bajo advertisement but also can enhance the marketing strategy for the Indonesian archipelago. This research helps develop visual elements that can become a reference for another strategy that focuses on the exotic islands and oceans in Indonesia.